Spectrin promotes the association of F-actin with the cytoplasmic surface of the human erythrocyte membrane - Fowler, VM (The Rockefeller University Press, 1981)
We studied the binding of actin to the erythrocyte membrane by a novel application of falling ball viscometry. Our approach is based on the notion that if membranes have multiple binding sites for F-actin they will be able to cross-link and increase the viscosity of actin. Spectrin- and actin-depleted inside-out vesicles reconstituted with purified spectrin dimer or tetramer induce large increases in the viscosity of actin. Comparable concentrations of spectrin alone, inside-out vesicles alone, inside-out vesicles plus heat-denatured spectrin dimmer or tetramer induce large increases in the viscosity of actin. Comparable concentrations of spectrin alone, inside-out vesicles alone, inside-out plus heat denatured spectrin, ghosts, or ghosts plus spectrin have no effect on the viscosity of actin. Centrifugation experiments show that the amount of actin bound to the inside-out vesicles is enhanced in the presence of spectrin. The interactions detected by low-shear viscometry reflect actin interaction with membrane- bound spectrin because (a) prior removal of band 4.1 and ankyrin (band 2.1, the high- affinity membrane attachment site for spectrin) reduces both spectrin binding to the inside-out vesicles and their capacity to stimulate increase in viscosity of actin in the presence of spectrin + actin are inhibited by the addition of the water-soluble 72,000- dalton fragment of ankyrin, which is known to inhibit spectrin reassociation to the membrane. The increases in viscosity of actin induced by inside-out vesicles reconstituted with purified spectrin dimer or tetramer are not observed when samples are incubated at 0 degrees C. This temperature dependence may be related to the temperature-dependent associations we observe in solution studies with purified proteins: addition of ankyrin inhibits actin cross-linking by spectrin tetramer plus band 4.1 at 0 degrees C, and enhances it at 32 degrees C. We conclude (a) that falling ball viscometry can be used to assay actin binding to membranes and (b) that spectrin is involved in attaching actin filaments or oligomers to the cytoplasmic surface of the erythrocyte membrane.